Ferramenta simplificada para avalição dos efeitos hidrologicos e dos custos de implantação de tecnicas compensatorias na gestão de aguas pluviais urbanas - Lopes, Bruna Lamorea Veiga (Universidade Federal de São Carlos, 2025)
The significant expansion of urban areas has intensified and increased the frequency of the negative impacts associated with stormwater runoff. Stormwater drainage systems, where they exist, have become insufficient to handle growing peak flows and volumes, and they typically aim only to convey runoff downstream, thereby transferring the problem to other areas. Alternative solutions have been studied and implemented, incorporating detention, infiltration, and evapotranspiration processes. So-called Compensatory Techniques (CTs) fall within this category and have been increasingly adopted. However, questions remain regarding their design criteria, hydrological effects, and associated costs. The objective of this research was to propose and apply a method that enables a rapid and objective assessment of the effects resulting from the implementation of different CTs in urban areas. The underlying principle of the method is that the primary characteristic of a CT in defining its hydrological effect is its detention volume, considering its storage capacity and, to a much lesser extent, its infiltration capacity. To this end, an Excel spreadsheet was developed in which basic local hydrological data are entered, generating surface runoff flows that, in turn, allow for the design of a Virtual Detention Basin (VDB). This VDB serves as a reference for the proposed assessment, by comparing the reduction in its required volume resulting from the introduction of CTs. The spreadsheet is organized into tabs to facilitate its use, and four CT typologies have been incorporated to date: depressed green areas, infiltration wells, rain gardens, and trenches. In addition to hydrological aspects, the spreadsheet estimates the costs of the different CTs and compares them with the costs of the Virtual Detention Basin. The tool was applied to several urban situations in the municipality of Araraquara, São Paulo State, Brazil, yielding satisfactory results and demonstrating the ability to analyze different scenarios in a rapid manner. At the conclusion of the dissertation, a set of variables and indicators was also presented for application specifically in already urbanized areas, complementing the spreadsheet’s use and contributing to the planning and implementation of Compensatory Techniques.
Simplified tool for evaluating the hydrological effects and implementation costs of compensatory techniques in urban stormwater management
Keywords: Técnicas Compensatórias; Drenagem Urbana Sustentável; Bacia de Detenção; Áreas Verdes Rebaixadas; Cálculo Automatizado de Drenagem; Compensatory Techniques; Sustainable Urban Drainage; Detention Basin; Lowered Green Areas; Automated Drainage Calculation; ENGENHARIAS; 11. Cidades e Comunidades Sustentáveis